Permanent Magnet Tubular Generator with Quasi-Halbach Array for Free-Piston Generator System - Behrooz Rezaeealam (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
In this paper, the performance of a free-piston generator system with tubular single-phase stator winding is investigated for three different configurations of permanent magnet arrays on the mover: radial, rectangular quasi-Halbach and trapezoidal quasi-Halbach arrays. The optimal shape of the rectangular quasi-Halbach magnetization is obtained by employing an optimization technique called Imperialist Competitive Algorithm (ICA), and the results are compared with the previously developed permanent magnet linear generator (PMLG) with magnets of radial magnetization. Then, the resultant design of rectangular quasi-Halbach array, is changed to trapezoidal quasi-Halbach array and its performance is compared with other types of magnet arrays. The employed ICA is based on the analytical model of the magnetic flux distribution in air-gap, and is further verified by a nonlinear transient finite element (FE) model. The FE model has been developed to study the performance of the reciprocating PMLG. The accuracy of the proposed FE model is exemplified by comparing the calculated results with the experimental ones regarding the PMLG with radial magnetization.